2023
DOI: 10.48550/arxiv.2301.08745
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is ChatGPT A Good Translator? Yes With GPT-4 As The Engine

Abstract: This report provides a preliminary evaluation of ChatGPT for machine translation, including translation prompt, multilingual translation, and translation robustness. We adopt the prompts advised by ChatGPT to trigger its translation ability and find that the candidate prompts generally work well and show minor performance differences. By evaluating on a number of benchmark test sets 1 , we find that ChatGPT performs competitively with commercial translation products (e.g., Google Translate) on high-resource Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 5 publications
0
50
0
Order By: Relevance
“…(c) Personal Skill Development: • Improve language skills: ChatGPT can play a significant role to improve individual language skills. This model is able to perform machine translation to overcome language barriers and make information more accessible 20 . Again, this model can improve users' language proficiency by answering questions and providing practice (speaking and writing) sessions in real time 19 .…”
Section: Opportunitymentioning
confidence: 99%
See 1 more Smart Citation
“…(c) Personal Skill Development: • Improve language skills: ChatGPT can play a significant role to improve individual language skills. This model is able to perform machine translation to overcome language barriers and make information more accessible 20 . Again, this model can improve users' language proficiency by answering questions and providing practice (speaking and writing) sessions in real time 19 .…”
Section: Opportunitymentioning
confidence: 99%
“…• Provide language translation: ChatGPT can translate text from one language to another, providing real-time translation services and improving communication between individuals using different languages 20 . Moreover, ChatGPT can aid human translators by offering alternate phrasing, defining uncommon terms, and enhancing the accuracy of the translation process.…”
Section: Opportunitymentioning
confidence: 99%
“…The results are given in parenthesis at the end of each paragraph below: The instruction given to ChatGPT referred to a very broad area making it relatively easy for ChatGPT to generate an adequate and relatively straightforward answer, which could indeed pass for an editorial, but certainly for the start of an introduction section of a student paper. The system may have a more challenging time with a narrower topic in the sports field, as shown by linguistics, mathematics, law, and medicine studies (Choi et., al, 2023;Frieder et al, 2023;Jeblick et al, 2022;Jiao et al, 2023). But each academic area is unique; some are philosophical while others are more factual, such as those in natural sciences, and ChatGPT must adapt to handling this range of information.…”
Section: Essay Commandmentioning
confidence: 99%
“…On the negative side, a recent study concluded that ChatGPT might not perform as well as commercial systems for biomedical abstracts or Reddit comments regarding translation accuracy. Still, translating spoken language may be of good service (Jiao et al, 2023). Additionally, apart from linguistics, ChatGPT was test-driven in mathematics, and the conclusion was that the system's math ability was lower than that of an average graduate student in mathematics (Frieder et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Large language models, including ChatGPT, have received both recognition and criticism for their capacity to produce human-like text (Jiao et al, 2023;Pavlik, 2023;OpenAI, 2022). While these models are trained on vast amounts of data, they have been criticized for their lack of understanding of the language they generate (Binz & Schulz, 2023).…”
Section: Introductionmentioning
confidence: 99%